2018
DOI: 10.1080/01443615.2017.1389867
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum thromboprophylaxis in a multireligious cohort: a retrospective review of indications and uptake

Abstract: Strategies to prevent mortality from obstetric venous thromboembolism begin with identification, risk stratification and subsequently, implementation of prophylactic measures. We sought to identify the burden of pharmacologic thromboprophylaxis in postpartum women, including the main clinical indications and its uptake in a multireligious population, with Islam as the official religion. A total of 2514 deliveries between 1st January to 31st December 2016, across three centres in Malaysia were reviewed retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…During its application in other Asian countries, it was found that the RCOG RAM might lead to the overuse of anticoagulant drugs in women who are less likely to develop postpartum VTE. A retrospective study in Malaysia suggested that 30.62% of postpartum women without VTE met the criteria for thromboprophylaxis [ 18 ]. Our study reached a similar conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…During its application in other Asian countries, it was found that the RCOG RAM might lead to the overuse of anticoagulant drugs in women who are less likely to develop postpartum VTE. A retrospective study in Malaysia suggested that 30.62% of postpartum women without VTE met the criteria for thromboprophylaxis [ 18 ]. Our study reached a similar conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…In a setting with a sizable Muslim population, low molecular weight heparin was the thromboprophylaxis of choice in more than two-third of the patients. 34 The extended hospitalization in our practice was mostly defensive medical practice and fear of litigations. This increased risk continues for up to 6 to 12 weeks postpartum.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 In pregnant women, venous thromboembolism (VTE) presents as deep vein thrombosis (DVT) or pulmonary embolism (PE). 3 , 4 In recent decades, VTE has become a leading cause of sudden death, which occurs in every 1600 pregnancies, and PE accounted for 9% of overall maternal deaths. 5 , 6 It is well recognized that pregnancy increases the risk of thromboembolism under conditions of hypercoagulability, decreased mobility, and compression of the inferior vena cava and pelvic veins.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 It is well recognized that pregnancy increases the risk of thromboembolism under conditions of hypercoagulability, decreased mobility, and compression of the inferior vena cava and pelvic veins. 3 , 4 Therefore, there is an urgent need to recognize risk factors of pregnancy-related VTE.…”
Section: Introductionmentioning
confidence: 99%